A dose‐escalation phase IIa study of 2, 2‐dimethylbutyrate (HQK‐1001), an oral fetal globin inducer, in sickle cell disease. Issue 11 (3rd October 2013) - Kutlar, Abdullah; Reid, Marvin E.; Inati, Adlette; Taher, Ali T.; Abboud, Miguel R.; El‐Beshlawy, Amal; Buchanan, George R.; Smith, Hedy; Ataga, Kenneth I.; Perrine, Susan P.; Ghalie, Richard G.
<x xml:space="preserve">Abstract</x> 2, 2‐dimethylbutyrate (HQK‐1001), an orally‐bioavailable promoter‐targeted fetal globin gene‐inducing agent, was evaluated in an open‐label, randomized dose‐escalation study in 52 subjects with hemoglobin SS or S/β0 thalassemia. HQK‐1001 was administered daily for 26 weeks at 30 mg/kg (n = 15), 40 mg/kg (n = 18) and 50 mg/kg (n = 19), either alone (n = 21) or with hydroxyurea (n = 31). The most common drug‐related adverse events were usually mild or moderate and reversible. Gastritis was graded as severe in three subjects at 40 mg/kg and was considered the dose‐limiting toxicity. Subsequently all subjects were switched to the maximum tolerated dose of 30 mg/kg. Due to early discontinuations for blood transfusions, adverse events or non‐compliance, only 25 subjects (48%) completed the study. Drug plasma concentrations were sustained above targeted levels at 30 mg/kg. Increases in fetal hemoglobin (Hb F) were observed in 42 subjects (80%), and 12 (23%) had increases ≥4%. The mean increase in Hb F was 2% [95% confidence interval (CI), 0.8–3.2%] in 21 subjects receiving HQK‐1001 alone and 2.7% (95% CI, 1.7–3.8%) in 31 subjects receiving HQK‐1001 plus hydroxyurea. Total hemoglobin increased by a mean of 0.65 g/dL (95% CI, 0.5–1.0 g/dL), and 13 subjects (25%) had increases ≥1 g/dL. Future studies are warranted to evaluate the therapeutic potential of HQK‐1001 in sickle cell disease. Am. J. Heamtol. 88:E255–E260, 2013. © 2013 Wiley Periodicals, Inc.